Limit Analysis using the extended Matsuoka-Nakai yield criterion under plane strain conditions - Mário Vicente da Silva; Armando Antão (Geotecnia, 2023)
This paper investigates the implementation of the Extended-Matsuoka-Nakai yield criterion on Limit Analysis formulation under plane strain conditions. The current approach is based on a three-field mixed finite element model and the Alternating Direction Method of Multipliers optimization algorithm. For this purpose, an equivalence between the classical Mohr-Coulomb criterion and the Extended-Matsuoka-Nakai is established and explored. Three numerical applications are presented to test and to illustrate the capabilities of this approach. The results are confronted with other authors’ solutions or experimental data.